2013
DOI: 10.3109/01612840.2013.799721
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Perspectives on the Care of Adults with Mental Health Problems and Histories of Childhood Sexual Abuse

Abstract: Despite growing awareness and evidence linking childhood sexual abuse (CSA) to numerous ongoing health problems in adulthood, the integration of this knowledge into nursing practice remains inconsistent. This article reports the results of a study that explored nurses' perspectives on, and experiences with, providing care for adults with mental health problems who may also have histories of CSA. Nurses' views underscore the challenges and complexities involved when providing care for this population. The theme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
6
1
Order By: Relevance
“…Lack of theoretical knowledge and skills, organizational support and clinical supervision were identified as perceived barriers to the preparedness of MHNs to work with the issue of CSA. Unlike previous research, which reported that MHNs were reluctant or avoidant to engage with adults who had CSA histories (Chernomas & Mordoch, 2013;Chouliara et al, 2011;Lee, Coles, Lee, & Kulkarni, 2012), this study highlighted that MHNs were willing to engage with the issue of CSA, despite feeling unprepared to do so at times. In this study, MHNs undervalued their interpersonal skills when engaging with this client group based on their perception that they did not have a specific set of specialized skills to work with this client group effectively.…”
Section: Discussioncontrasting
confidence: 93%
“…Lack of theoretical knowledge and skills, organizational support and clinical supervision were identified as perceived barriers to the preparedness of MHNs to work with the issue of CSA. Unlike previous research, which reported that MHNs were reluctant or avoidant to engage with adults who had CSA histories (Chernomas & Mordoch, 2013;Chouliara et al, 2011;Lee, Coles, Lee, & Kulkarni, 2012), this study highlighted that MHNs were willing to engage with the issue of CSA, despite feeling unprepared to do so at times. In this study, MHNs undervalued their interpersonal skills when engaging with this client group based on their perception that they did not have a specific set of specialized skills to work with this client group effectively.…”
Section: Discussioncontrasting
confidence: 93%
“…[121] Moreover, successful implementation of a psychotherapy intervention in Ethiopian primary care may provide support and a framework for interventions in highincome countries, where comorbid PTSD and SMI is still usually overlooked, and integration of EBIs for comorbid PTSD and SMI remains minimal. [10,13,[24][25][26][27][28][29][30][31][32] One of the central design considerations for this study was the selection of the BREATHE intervention [122,123] for adaptation and implementation. Although rst-line PTSD treatments such as CPT and PE have the largest evidence-base for PTSD treatment, trials have generally excluded people with SMI, and the interventions are highly intensive, leading to implementation challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Successful implementation of a psychotherapy intervention in Ethiopian primary care may provide a framework for interventions in other low-resource primary care settings, including those in HICs, where comorbid PTSD and SMI is usually overlooked, and integration of EBIs for comorbid PTSD and SMI remains minimal. [10,13,[24][25][26][27][28][29][30][31][32] Despite the fact that PTSD may be higher in con ict-affected LMICs, and at least as prevalent in noncon ict LMIC settings, as compared to HICs, [33][34][35][36][37] many LMICs have extremely limited mental health services making implementation of EBIs challenging. [38,39] Low-income countries have less than one mental health provider per 100,000 people (compared to more than 50 in HICs), and almost all mental health services in low-income countries are provided in hospitals in large cities, with virtually no care available in rural areas.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed there is very high comorbidity between PTSD and psychosis (Grubaugh et al 2011; Bajor et al 2013) and PTSD and substance abuse (Schafer & Najavits, 2007; Dass-Brailsford & Myrick, 2010; McCauley et al 2012), and often PTSD is undiagnosed in these populations (Frueh et al 2002; Salyers et al 2004; Chessen et al 2011; Chernomas & Mordoch, 2013). As a result of this finding, greater attention is being paid to comorbid and underlying diagnoses at Icyizere.…”
Section: Discussionmentioning
confidence: 99%
“…Discussions with Icyizere staff also indicated that many psychotic disorders and substance use disorders were preceded by traumatic events and PTSD symptoms and these disorders may be complications from earlier trauma reactions. Indeed there is very high comorbidity between PTSD and psychosis (Grubaugh et al 2011; Bajor et al 2013) and PTSD and substance abuse (Schafer & Najavits, 2007; Dass-Brailsford & Myrick, 2010; McCauley et al 2012), and often PTSD is undiagnosed in these populations (Frueh et al 2002; Salyers et al 2004; Chessen et al 2011; Chernomas & Mordoch, 2013). As a result of this finding, greater attention is being paid to comorbid and underlying diagnoses at Icyizere.…”
Section: Discussionmentioning
confidence: 99%